The phytohormone-mediated action of the synthetic regulators on cell extension growth in higher plants - Tsygankova, V.A.; Zayets, V.N.; Galkina, L.A.; Blume, Y.B. (Биополимеры и клетка, 1999)
It was shown that the action of synthetic growth activators on growth and development of isolated «non-decapitated» embryonic axes was analogous to action on embryonic axes of the intact haricot bean seeds; for the 72-hours period size increase of the embryonic axes depended on incubative medium composition: distilled water< lutidine N-oxide-6-methylthiouracil< (IAA). Growth and development of «decapitated» embryonic axes in the same media sharply differed from the growth of «non-decapitated» axes: distilled water > lutidine N-oxide - 6-methylthiouracil < (IAA). In the experiments with embryonic axes in both of which one cotyledon was preserved («monocotyledonous seedlings») size increase was identical to size increase of embryonic axes in intact haricot bean seeds, as in the case of «non-decapitated» and «decapitated» embryonic axes, and it also depended on the incubative medium composition: distilled water < lutidine N-oxide - 6-methylthiouracil < (IAA). Investigation of the fractional composition of new synthesized [¹⁴C] impulse labelled proteins using the method of one-dimensional PAG-etectrophoresis and gel fluorography approach showed that lutidine N-oxide intensifies the synthesis of all cellular proteins fractions with predominating increase of the synthesis of some high-molecular and low-molecular polypeptides, and 6-methylthiouracil intensifies the synthesis of only one polypeptide with molecular weight of 30 kDa. The data obtained are examined accordingly as evidence in favour of ideas, developing in our investigation about phytohormone-mediated action of the synthetic plant growth regulators and different-direction mechanisms growth activating action of lutidine N-oxide and 6-methylthiouracil The scheme of phytohormone-mediated action of the synthetic regulators on cell extension growth in higher plants is proposed. Показано, що дія синтетичних активаторів росту на розвиток та ріст ізольованих «недекапітованих» зародкових осей була аналогічною за своїм характером до дії на зародкові осі інтактного насіння квасолі; за 72-годинний період збільшення розмірів зародкових осей залежало від складу середовища інкубації: дистильована вода < N-окис лутидину - 6-метилтіо- урацил < ЮК. Ріст і розвиток «декапітованих» осей на тих самих середовищах різко відрізнявся від росту «недекапітованих»: дистильована вода > N-окис лутидину - 6-метилтіо-урацил < ЮК В експериментах із зародковими осями, у яких збережено по одній сім'ядолі («однодольні» кільчики), як у випадку з «недекапітованими», так і «декапітованими» зародковими осями збільшення розмірів було ідентичним такому зародкових осей інтактного насіння квасолі і також залежало від складу інкубаційного середовища: дистильована вода < N-окис лутидину - 6-метилтіоурацил < ЮК Вивчення фракційного складу новосинтезованих [ ¹⁴С ]-мічених білків зародкових осей методом одномірного ПАГ-електрофорезу з наступною флюорографією гелів засвідчило, що N-окис лутидину підсилює синтез усіх фракцій клітинних білків з переважаючим збільшенням синтезу деяких високо- і низькомолекулярних поліпептидів, а 6-метилтіоурацил підсилює синтез тільки одного поліпептиду з молекулярною масою 30 кДа. Отримані дані можуть розглядатися відповідно як доказ висунутих нами положень стосовно фітогормон-опосередкованої дії синтетичних регуляторів росту рослин та різноспрямованості механізмів рістактивуючої дії N-окису лутидину та 6-метил-тіоурацилу. Запропоновано схему опосередкованого фітогормонами механізму дії синтетичних регуляторів на ріст клітин розтягненням у вищих рослин. Показано, что действие синтетических ростактиваторов на рост и развитие изолированных «недекапитированных» зародышевых осей было аналогичным по своему характеру действию на зародышевые оси интактных семян фасоли; за 72-часовой период увеличение размеров зародышевых осей зависело от состава среды инкубации зародышей: диситиллированная вода < N-окись лутидина - 6-метилтиоурацил < МУК. Рост и развитие «декапитированных» зародышевых осей на тех же средах резко отличались от роста «недекапитированных» осей: дистиллированная вода > N-окись лутидина - 6-метилтиоурацил < МУК В опытах с зародышевыми осями, у которых было сохранено по одной семядоле («однодольные» проростки), как в случае с «недекапитированными», так и «декапитированными» зародышевыми осями увеличение размера было идентично таковому зародышевых осей в интактных семенах фасоли и также зависело от состава инкубационной среды: диситиллированная вода < N-окись лутидина в 6-метилтиоурацил < [¹⁴C] Изучение фракционного состава новосинтезированных ([¹⁴С]-импульсно меченных) белков зародышевых осей методом одномерного ПАГ-электрофореза с последующей флюорографией гелей показало, что N-окись лутидина усиливает синтез всех фракций клеточных белков с преобладающим увеличением синтеза некоторых высоко- и низкомолекулярных полипептидов, а 6-метилтиоурацил усиливает синтез только одного полипептида с молекулярной массой 30 кДа. Полученные данные рассматриваются соответственно как доказательство в пользу развиваемых нами представлений о фитогормон-опосредуемом действии синтетических регуляторов роста растений и о разнонаправленности механизмов ростактивирующего действия N-окиси лутидина и 6-метилтиоурацила. Предложена схема опосредуемого фитогормонами механизма действия синтетических регуляторов на рост клеток растяжением у высших растений.